Enhancement of antimicrobial activity in endophytes HAB11R3 and HAB10R12 / Siti Nadia Adilah Md Nor - Md Nor, Siti Nadia Adilah (2008)
The effect of culture condition on antimicrobial activity of endophytes HAB 11 R3 and HAB 1 OR 12 were investigated. The parameter that were investigated are incubation period (PDAl; incubated for I week, PDA2; incubated for 2 weeks, PDA4; incubated for 4 weeks), different media (solid; PDB2 (incubated in broth media), liquid; PDA2 (incubated in agar media)), different water source (tap water; TPDA and TPDB, deionized water; PDA2 and PDB2) and different strength (1/5 from original strength; 1/5PDA and l/5PDB). Two different methods were employed to detect the antimicrobial activity; the disc diffusion test and minimum inhibitory concentration (MIC) test. The secondary metabolites of HAB 11 R3 were showed killing activity towards one or more pathogenic bacteria. Endophytic metabolites that were cultured in broth media showed inhibitory activity against Bacillus subtilis (35mm) and Micrococcus luteus (38mm). The metabolites cultured in broth media also give the lowest minimum inhibitory concentration (MIC) against Bacillus subtilis (0.08mg/ml), Micrococcus luteus (0.04mg/ml) and Escherichia coli (0.63mg/ml) whereas the mycelium of endophyte that cultured in broth media give lowest MIC against Staphylococcus aureus (0.3 lmg/ml). No activity of antimicrobial activity was reported on endophytic strain HAB10R12.